2017
DOI: 10.3791/55039
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Monocyte Monolayer Assay to Evaluate Fcγ Receptor-mediated Phagocytosis

Abstract: Although originally developed for predicting transfusion outcomes of serologically incompatible blood, the monocyte monolayer assay (MMA) is a highly versatile in vitro assay that can be modified to examine different aspects of antibody and Fcγ receptor (FcγR)-mediated phagocytosis in both research and clinical settings. The assay utilizes adherent monocytes from peripheral blood mononuclear cells isolated from mammalian whole blood. MMA has been described for use in both human and murine investigations. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Also, MMA showed very high levels of phagocytosis of anti‐AnWj–sensitized RBCs despite an IAT result showing that only a small amount (1+) of AnWj antibodies were bound to the RBCs. This phenomenon has been described in the past where studies have shown that the strength of opsonization does not necessarily correlate with significant monocyte interactions leading to phagocytosis …”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Also, MMA showed very high levels of phagocytosis of anti‐AnWj–sensitized RBCs despite an IAT result showing that only a small amount (1+) of AnWj antibodies were bound to the RBCs. This phenomenon has been described in the past where studies have shown that the strength of opsonization does not necessarily correlate with significant monocyte interactions leading to phagocytosis …”
Section: Discussionmentioning
confidence: 84%
“…Additionally, we investigated the use of more readily available O+, D unphenotyped RBCs for MMA, which alleviated the need for finding an R 2 R 2 donor for each experiment or for the additional procedures of cryopreserving and preparing such control RBCs. Using the same PI acceptability criteria for R 2 R 2 ‐positive controls as in previous studies, we determined that all O D+ cells from the RBCs used in this study showed high rates of opsonization (IAT = 4+) and did not affect phagocytosis by the monocytes (PI > 60) and therefore could be deemed appropriate and valid positive controls. This further facilitates the implementation and interpretation of this assay, as we are able to set quantitative limits to control for the interdonor variability on phagocytosis in the MMA.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations